Tobacco Use Among Arab Immigrants Living in Colorado: Prevalence and Cultural Predictors. (March 2017) - El Hajj, Dana G.; Cook, Paul F.; Magilvy, Kathy; Galbraith, Michael E.; Gilbert, Lynn; Corwin, Marla
Purpose: The authors determined the prevalence of smoking among Arab immigrants living in Colorado. The authors also evaluated the relationship between acculturation and tobacco use, including both cigarettes and hookah among Arab immigrants.Method: A cross-sectional survey of 100 adult Arab immigrants living in Colorado was carried out.Results: The results revealed that 19% of the study participants were current cigarette smokers and 21% were current hookah smokers. Participants who were more integrated into Arab culture were more likely to use tobacco products ( p = .03) and to have family members ( p = .02) and friends who use tobacco products ( p = .007).Conclusions: Acculturation plays a major role in affecting the health habits of Arab immigrants living in Colorado, especially in the area of hookah smoking.Implications for Practice: Understanding some culturally relevant predictors of tobacco use might assist health care providers in designing successful smoking cessation programs.